(untitled) (Шийдвэр гүйцэтгэл судлал, 2025)
Among the threats that have become topical in the world in recent decades, against the state and society, organized crime and corruption have come to the fore. In the post-Soviet countries, there is also a process of criminalization in society and the state. Thus, the concept of national security of the Kyrgyz Republic specifically highlights the threats of organized crime, international terrorism and corruption as the most dangerous threats to the existence of the state and its stability